2023
DOI: 10.7759/cureus.36778
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Implications of Anti-thyroid Peroxidase Antibodies in Graves’ Disease in Basrah

Abstract: BackgroundGraves' disease (GD) is an autoimmune disease, with thyrotropin receptor antibodies (TRAbs) being the most important cause in the pathogenesis. The aim of this study is to assess the clinical significance of anti-TPO Abs in GD. MethodsA retrospective study was conducted at the Faiha specialized Diabetes, Endocrine, and Metabolism Center (FDEMC) in Basrah during the period between December 2021 and December 2022. A total of 141 patients with GD were involved in this study, and of them, 97 (68.8%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Azizi et al found that patients with positive aTPO were associated with high baseline free T4, while not with thyroid eye disease [18]. Similar results were demonstrated by Alhubaish et al patients with aTPO antibodies versus those with negative antibodies showed higher pretreatment-FT4 level (3.7 ± 0.2 vs. 3.0 ± 0.2 with p = 0.021), baseline TRAb level of more than 6.4 IU/mL, and giraffe appearance on thyroid ultrasound [19].…”
Section: Discussionsupporting
confidence: 78%
“…Azizi et al found that patients with positive aTPO were associated with high baseline free T4, while not with thyroid eye disease [18]. Similar results were demonstrated by Alhubaish et al patients with aTPO antibodies versus those with negative antibodies showed higher pretreatment-FT4 level (3.7 ± 0.2 vs. 3.0 ± 0.2 with p = 0.021), baseline TRAb level of more than 6.4 IU/mL, and giraffe appearance on thyroid ultrasound [19].…”
Section: Discussionsupporting
confidence: 78%
“…Carvalho et al, anti-TPO Abs were present in about 80% of patients, [23] Samsudin et al, anti-TPO Abs were present in about 62% of patients, [24] Almomin et al, 2019 anti-TPO Abs were present in about 60.4% of patients, [25] Siriwardhane et al, anti-TPO Abs were present in about 59.8%. of patients, [26] Sulejmanovic et al, anti-TPO Abs were present in about 71% of patients, [27] and Alhubaish et al, anti-TPO Abs were present in about 58.9% with GD [28] .…”
Section: Discussionmentioning
confidence: 98%